Arch Wire: A Novel Technique for Intra-Maxillary Fixation - Shenoi, S. R. (J Maxillofac Oral Surg, 2015)
INTRODUCTION: Arch bars are regularly used in the management of dentoalveolar and minimally displaced fractures of the maxilla or mandible and luxation or avulsion of teeth by maxillofacial surgeons. The procedure for arch bar placement has remained unchanged over the period of years, and this coupled with the difficulty in maintenance of oral hygiene is a problem that begs attention. TECHNIQUE: We have devised a technique to overcome these hurdles and achieve adequate intramaxillary splinting. The technique uses an arch wire and ligature wire assembly instead of the conventional arch bar. CONCLUSION: This technique is easy to learn and can thus be used as a rapid yet robust alternative to the conventional arch bar for dentoalveolar and minimally displaced fractures.